1999
DOI: 10.1097/00007435-199905000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Group Differences in the Prevalence of Sexually Transmitted Diseases in the United States: A Network Explanation

Abstract: African Americans' higher infection rate for bacterial diseases can be explained by the patterns of sexual networks within and between different racial/ethnic groups. First, infections are more widespread in the African American population at large because partner choice is more highly dissortative--meaning that "peripheral" African Americans (who have had only one partner in the past year) are five times more likely to choose "core' African Americans (who have had four or more partners in the past year) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
336
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 533 publications
(352 citation statements)
references
References 14 publications
15
336
1
Order By: Relevance
“…10,12,16,17 Recent studies have underscored the importance of focusing on and understanding sexual networks by race and prior research has observed a significant tendency among Black MSM to have more partners of the same race. 13,22,24 Consistent with previous studies, 13,22,24 Black MSM in the current sample had more partners who were Black men (49%) and fewer Hispanic/Latino (40%) or White (13%) male partners. However, in contrast with prior research, relative to participants who had sex last with a White male, participants who had sex last with a Hispanic/Latino male were more likely to have engaged in UAS and those who had sex with a Black male were less likely to report engaging in UAS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…10,12,16,17 Recent studies have underscored the importance of focusing on and understanding sexual networks by race and prior research has observed a significant tendency among Black MSM to have more partners of the same race. 13,22,24 Consistent with previous studies, 13,22,24 Black MSM in the current sample had more partners who were Black men (49%) and fewer Hispanic/Latino (40%) or White (13%) male partners. However, in contrast with prior research, relative to participants who had sex last with a White male, participants who had sex last with a Hispanic/Latino male were more likely to have engaged in UAS and those who had sex with a Black male were less likely to report engaging in UAS.…”
Section: Discussionsupporting
confidence: 88%
“…10,12,16,17 Prior research has shown that sexual mixing between members of different populations may facilitate the spread of HIV and STDs. [18][19][20][21][22] Early research with MSM found sexual relationships between MSM of different age groups to be associated with higher risk for HIV infections. 20,21 Studies have more recently begun to underscore the importance of focusing on and understanding racial dynamics in sexual networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Americans have higher STI prevalence after adjustment for sexual activity (7,35). It has been shown that sexual mixing is assortative according to race/ethnicity (7,20) …”
Section: Discussionmentioning
confidence: 99%
“…We term one particular form of confounding bias the "assortativity bias", because it stems from assortativity in sexual mixing (partner choice). That is, on average, people have partners with similar characteristics (e.g., age) and behavior (e.g., smoking status) as themselves (5)(6)(7)(8).…”
Section: Word Count=200mentioning
confidence: 99%